BIODIVERSITY AND ANTIBACTERIAL ACTIVITIES OF ENDOPHYTIC FUNGI ASSOCIATED WITH UNCARIA GAMBIER (HUNTER) ROXB. VAR. UDANG FROM JASINGA, BOGOR, INDONESIA - Palupi, Kartika Dyah; Kamal, Andi Saptaji; Marlina, Lina; Hafid, Lukman; Evana; Tarigan, Elsera Br; Raunsai, Marlin Megalestin; Ilyas, Muhammad; Kanti, Atit; Agusta, Andria (Berita Biologi, 2023)
Endophytic fungi living in medicinal plant tissues are potential bioactive metabolite sources for drug discovery and development. However, the research regarding endophytic fungi associated with Indonesian medicinal plants is still limited. This study aimed to explore the biodiversity of endophytic fungi associated with the medicinal plant Uncaria gambir (Hunter) Roxb. var. udang and their antibacterial activities. Twenty-seven endophytic filamentous fungi were isolated from the surface-sterilized leaves, stems, and roots of Uncaria gambir (Hunter) Roxb. var. udang collected in Jasinga, Bogor, West Java, Indonesia. The observation based on the morphological characters both macroscopically and microscopically, as well as chemical profiling using thin layer chromatography (TLC), revealed that some of the isolated endophytic fungi were identical. Overall, the isolated endophytic fungi consist of six Coelomycetes, three Dematiaceae, four Pestalotiopsis sp., two Penicillium sp., one Aspergillus terreus, and two fungi were unidentified. Antibacterial activities of the ethyl acetate extract from the isolated endophytic fungi associated with Uncaria gambir (Hunter) Roxb. var. udang were observed against E. coli, B. subtilis, S. aureus, and M. luteus. Twelve types of isolated endophytic fungi from Uncaria gambir (Hunter) Roxb. var. udang exhibited antibacterial activities.